The Factors affecting the separation of the reaction mixture after transesterification of rapeseed oil - Hájek, Martin; Skopal, František (Wiley-Blackwell, 2008)
The most used method of biodiesel production is the transesterification of vegetable oils by basic homogeneous catalyst. Heterogeneous reaction mixture is formed by this process and contains two phases: ester phase and glycerol phase. From this mixture, biodiesel is gained by sedimentation. Quality and quantity of both phases are affected by conditions of sedimentation process. It was studied how conditions (independent variables: temperature of separation, amount of added water, time of sedimentation, etc.) affect the quantity and the quality of both phases (dependent variables). The statistic system Plackett - Burman was used for experiments planning. The relationship between independent and dependent variables was found and described by multidimensional linear regression. The created model allows to calculate the optimum conditions of biodiesel production so the quality of biodiesel fills the EN 14214.
Keywords: Biodiesel; sedimentation; separation; multivariable system